A new two-sided projection technique for model reduction of quadratic-bilinear descriptor systems. Issue 10 (3rd October 2019) - Ilyas Ahmad, Mian; Benner, Peter; Feng, Lihong
ABSTRACT: We investigate the problem of projection-based interpolation for model reduction of quadratic-bilinear descriptor systems. Existing two-sided projection techniques are analysed and a modified sequence of projection matrices is proposed. It is observed that the proposed technique generates better reduced order systems. Numerical results for some benchmark examples are presented in support of our observation.